Characterization of PVA-Chitosan Nanofibers Prepared by Electrospinning - K. Paipitak; T. Pornpra; P. Mongkontalang; W. Techitdheer; W. Pecharapa (My University, 2011)
PVA/Chitosan nanocomposite fibers were prepared by electrospinning method. The weight ratio of PVA:Chitosan was fixed at 80:20 in 2% Acetic acid. The concentration of the PVA/Chitosan solution was varied from 3 to 5 wt%. The viscosity of precursor solution was determined by Ubbelohe viscometer. The results revealed that the mixture solution viscosity is directly proportional to its concentration. The morphology and diameter of PVA/Chitosan nanocomposite fibers were characterized by scanning electron microscopy and atomic force microscopy. The diameter of as-prepared PVA/Chitosan nanocomposite fiber was approximately 100 nm. The suitable concentration condition of the solution for fiber formation is 5wt% due to the maximum fiber yield. Fourier Transform Infrared Spectroscopic measurement exhibited the existence of relevant functional groups of both PVA and Chitosan in the composites.
Keywords: Electrospinning; Electrospun Nanofibers in Biomedical Applications